Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0158
|View full text |Cite
|
Sign up to set email alerts
|

Deciding Between Prefabrication and On-Site Construction: A Choosing-by-Advantage Approach

Abstract: Several academic and industrial studies have documented the benefits of prefabrication compared to on-site construction. However, key construction project actors find it difficult to analyse whether prefabrication would be beneficial for their project with specific circumstances and targets. This research aims to develop a process to evaluate the impact of prefabrication in projects. First, based on the literature review and focus group discussion, we define the impact factors of prefabrication. Second, we app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…While other studies integrated CBA with other methods. Chauhan et al (2019) applied CBA together with cost-benefit analysis to define a process for measuring the impact of prefabrication. Perez and Arroyo (2019) focused on analysing the environmental public policy design process using the CBA decision system integrated with the Design Structure Matrix (DSM) to make complex decisions.…”
Section: Literature Review Choosing By Advantages (Cba)mentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies integrated CBA with other methods. Chauhan et al (2019) applied CBA together with cost-benefit analysis to define a process for measuring the impact of prefabrication. Perez and Arroyo (2019) focused on analysing the environmental public policy design process using the CBA decision system integrated with the Design Structure Matrix (DSM) to make complex decisions.…”
Section: Literature Review Choosing By Advantages (Cba)mentioning
confidence: 99%
“…Among the benefits that CBA provides are the following: (1) It Generates transparency in the decision-making process and allows explicit consideration of multiple alternatives based on various impact factors (Parrish and Tommelein 2009;Arroyo et al 2012;Chauhan et al 2019;Arroyo et al 2014). (2) It helps generate consensus based on the decision and promotes continuous learning (Parrish and Tommelein 2009;Arroyo et al 2012;Chauhan et al 2019;Arroyo et al 2014). (3) It helps to document information on why and on what basis decisions are made, so that they can be reviewed at a later time or in a future project (Parrish and Tommelein 2009).…”
Section: Cba Benefitsmentioning
confidence: 99%
“…This can affect the construction process directly because the loss of quality and time due to harsh weather can be avoided. It can also indirectly influence the construction process because weather conditions can damage building materials (Chauhan et al 2019), decreasing material availability. Due to less time spent on site, the risk of weather-related accidents is also lower (Durdyev and Ismail 2019).…”
Section: Off-site Construction's Impact On Clpmentioning
confidence: 99%
“…During the third year, the prefabrication research theme from the previous year was continued by developing a multi-criteria tool to evaluate the versatile impacts of prefabrication (Chauhan et al, 2019). The research showed that the tool helps project stakeholders to communicate about multifaceted impacts of production methods and to make the final decision on whether to prefabricate or not.…”
Section: Innovations In Constructionmentioning
confidence: 99%